Isolation and Characterization of Novel Phages Targeting Pathogenic Klebsiella pneumoniae - Li, Na; Zeng, Yigang; Bao, Rong; Zhu, Tongyu; Tan, Demeng; Hu, Bijie (Frontiers in Cellular and Infection Microbiology, 2021)
Klebsiella pneumoniae is a dominant cause of community-acquired and nosocomial infections, specifically among immunocompromised individuals. The increasing occurrence of multidrug-resistant (MDR) isolates has significantly impacted the effectiveness of antimicrobial agents. As antibiotic resistance is becoming increasingly prevalent worldwide, the use of bacteriophages to treat pathogenic bacterial infections has recently gained attention. Elucidating the details of phage-bacteria interactions will provide insights into phage biology and the better development of phage therapy. In this study, a total of 22 K. pneumoniae isolates were assessed for their genetic and phenotypic relatedness by multi-locus sequence typing (MLST), endonuclease S1 nuclease pulsed-field gel electrophoresis (S1-PFGE), and in vitro antibiotic susceptibility testing. In addition, the beta-lactamase gene (blaKPC) was characterized to determine the spread and outbreak of K. pneumoniae carbapenemase (KPC)-producing enterobacterial pathogens. Using these ST11 carbapenem-resistant K. pneumoniae isolates, three phages (NL_ZS_1, NL_ZS_2, and NL_ZS_3) from the family of Podoviridae were isolated and characterized to evaluate the application of lytic phages against the MDR K. pneumoniae isolates. In vitro inhibition assays with three phages and K. pneumoniae strain ZS15 demonstrated the strong lytic potential of the phages, however, followed by the rapid growth of phage-resistant and phage-sensitive mutants, suggesting several anti-phage mechanisms had developed in the host populations. Together, this data adds more comprehensive knowledge to known phage biology and further emphasizes their complexity and future challenges to overcome prior to using phages for controlling this important MDR bacterium.